Auditor Responsibility and Liability in Social Welfare Systems in the View of Islamic Jurisprudence - Ainura MAMATOVA; Sardar Gul Amen Al JABBARI; Ghazi Abdulazeez Sulaiman BAG; Sami Hameed ABBAS; Abdullah Saeed ABDULLAH; Abdulrazzaq Tuama Hawas; Hadeel Saadoon Maarij; Ahmed Taher Kadhim; Rami Mohammed ABDULLAH (al-'adalah, 2025)
This phenomenological study aims to explore the dual responsibilities of auditors within the social welfare system while also examining the complex interplay between compliance with social welfare regulations and exposure to liability under Islamic jurisprudence. The study is contextualized within the context of social security fund legislation, where auditors are increasingly expected to maintain ethical behaviour that is compliant with Sharia law amidst an ambiguous regulatory framework. Using the Heckman selection model, the study examines the relationship between public entity ownership in social security funds and the risks arising from related compliance issues. The findings indicate a strong inverse correlation between auditors' choices of receiving remuneration and receiving disciplinary action. The robustness of the model convincingly demonstrates the pressing need for sound risk procedures and internal controls that align with Islamic finance values, which emphasize trust (amānah), responsibility (mas'ūliyyah), and accountability (hisbah). This article fills a gap in the literature on Islamic auditing, which emphasizes that auditors should act not only as enforcers of the law but also as moral agents protecting public welfare assets.